CFD simulation and model predictive control of the pipeline transportation system in a trailing suction hopper dredger. Issue 4 (9th June 2022) - Su, Zhen; Zhang, Xiyuan; Luan, Rongyu
Abstract: The phenomenon of blocking pipe would appear for a trailing suction hopper dredger (TSHD) rake arm pipe in the construction process. Thus, based on the theory of particle flow mechanics, a transient three-dimensional two-phase hydrodynamic and sediment mixture model was established in this paper. Besides, different particle sizes of sediment concentration and velocity in the piping in the rake arm of the law were analyzed to solve the problem of blocking pipe and the prevention of dredging to provide theoretical support. Then, a model predictive controller was designed to regulate the mudflow in the pipeline by controlling the mud pump speed and compared with the proportional-integral (PI) controller. According to the results, the particle size of sediment affects concentration distribution in the pipeline under the same construction conditions for the TSHD. Besides, the larger the particle size of the sediment, the more significant the difference in the sediment concentration distribution in the pipeline. Similarly, the flow velocity is another influencing factor behind the change in concentration distribution in the pipeline, the increase in the flow velocity will improve the uniformity of concentration distribution in the pipeline, and the critical velocity will maintain the concentration distribution within a reasonable range. In terms of transportation control, the designed predictive model controller is capable of reducing overshoot and shorten the time required for adjustment. To sum up, the research result not only provides a valuable reference for the theoretical analysis and a controller design of the pipeline transportation system in the TSHD but also verifies the feasibility of the computational fluid dynamics model used in the study of pipeline transportation mechanisms. HIGHLIGHTS: A transient three-dimensional two-phase hydrodynamic and sediment mixture model was established. Different particle sizes of sediment concentration and velocity in the piping in the rake arm of the law were analyzed to solve the problem of blocking the pipe and prevention of dredging. A model predictive controller was designed to regulate the mudflow in the pipeline by controlling the mud pump speed.